Erratum: Morbidity, mortality and quality of life in the ageing haemodialysis population: results from the ELDERLY study - Seckinger, Jörg; Ritz, Eberhard; Schwenger, Vedat (Clinical kidney journal, 2017)
In the original published version of this article the formatting of Table 4 was partially incorrect. This error has now been corrected in the final published version